Perkawinan Usia Dini Dalam Hukum Adat di Desa Adat Songan Kintamani Bangli - I Made Suwitra; I Ketut Maharata Adi Putra; Diah Gayatri Sudibya (Warmadewa Press, 2025)
Starting from the phenomenon of early marriage which is still rampant, marriage is a bond that forms a new family and is regulated by legal provisions, both in customary law and national law, but there are still frequent violations of early marriage in the community. With regard to this, the formulation of the problem in this study is how legal is early marriage in the traditional village of Songan? And how is the recording of early marriage in the traditional village of Songan? The method used in this writing is the normative method. Based on the results of the research, it can be concluded that regarding underage marriage, there are several differences in standardization and perspectives based on customary law or the Indonesian Marriage Law. In customary law there is no age limit for marriage.